Sensitivity of Overwork, Overtime, Supervisory Support and Incentive to the Employee Turnover Intention - Titah Unggul Wirandono; Mulyana (Universitas Darussalam Gontor, 2023)
This paper aims to examine the effect of Overtime (OT), Overwork (OW), Supervisory Support (SS) on Employee Turnover Intention (ETI) with Incentive as a moderating variable. Respondents in this study were employees of the Asset Operator at PLTU Tanjung Jati B Unit 1-2 as many as 155 people. This research is motivated by the high turnover of Operation and Management Trainee (OMT) Asset Operator Unit 1-2 employees compared to Asset Operator Units 3-4 from the first batch in 2010 to the fifth batch in 2018 which once reached 100% turnover in the third batch. The sampling technique used proportional random sampling and data analysis using Partial Least Square (PLS). The results of this research are expected to contribute to the policy makers of the Employee Incentive Scheme (EIS) in Asset Operator Units 1-2.